2021
DOI: 10.1101/2021.01.29.428877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dysregulation of PAX5 causes uncommitted B cell development and tumorigenesis in mice

Abstract: PAX5 is the master transcription factor controlling B cell identity. In humans, mutations in PAX5 account for 30% of B cell acute lymphoblastic leukemia (B-ALL) cases. Investigating the causal effects of PAX5 mutations has however been difficult due to the premature lethality of Pax5−/− mice. Here we describe a novel mouse strain with a premature STOP mutation in Pax5 (Y351*) that produces a truncated protein and reduction in protein function, yet still allows for some B cell development to occur. A population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…A recent study has modelled in mice a single point mutation found in the patient’s PAX5 gene, trying to better recapitulate the human preleukemic stage. In this report, aged Pax5 Y351 */Y351 * mice spontaneously develop B-ALL with 100% penetrance [ 33 ].…”
Section: Mouse Modeling Of Genetic Susceptibility To Childhood Leukemiamentioning
confidence: 99%
“…A recent study has modelled in mice a single point mutation found in the patient’s PAX5 gene, trying to better recapitulate the human preleukemic stage. In this report, aged Pax5 Y351 */Y351 * mice spontaneously develop B-ALL with 100% penetrance [ 33 ].…”
Section: Mouse Modeling Of Genetic Susceptibility To Childhood Leukemiamentioning
confidence: 99%